Patient safety culture in Iranian teaching hospitals: baseline assessment, opportunities for improvement and benchmarking - Edris Kakemam; Ahmed Hassan Albelbeisi; Samane Davoodabadi; Masoud Ghafari; Zahra Dehghandar; Pouran Raeissi (BMC, 2022)
Abstract Background Patient safety culture is an essential factor in determining the ability of hospitals to treat and reduce patient risks. Healthcare professionals, especially nurses, play an important role in patient safety because they are responsible for direct and ongoing patient care. Few studies in Iran examine the patient safety culture in Iranian teaching hospitals, particularly from the perspective of nursing staff. This research assessed patient safety culture in teaching hospitals in Iran from the nurses' point of view and compared the outcomes with similar regional and global studies. Furthermore, the study identified the factors influencing patient safety culture and its association with outcomes. Methods A cross-sectional study was accomplished in thirty-two teaching hospitals in five provinces of Iran. A total of 2295 nurses were chosen through convenience sampling. Collection data were done using the Hospital Survey of Patient Safety Culture (HOPSC) from October 2018 and September 2019. We analyzed the data using descriptive statistics, independent sample t-test, one-way ANOVA, and multiple linear regression analysis. Results The results demonstrated the overall percentage of positive response rate for the HOPSC tool (36.4%). The average percentage of positive responses among all dimensions ranged from 27.1% in "Staffing" to 53.8% in "Teamwork across Hospital Units". Benchmarking analysis shows that Iranian hospitals are equal or better performance than the benchmark on several composites compared to regional and global findings. The results of multiple linear regression analysis showed that the age, gender, total years of experience in nursing, work area or unit, work hours, and size of the hospital were significant predictors of the perceptions patient safety culture of nurses (p <  0.05). Conclusions This is one of few studies that examine nurses' perceptions of patient safety culture in public hospitals in Iran. Although the results of the present study showed that the results of Iran were at or better than the many composites in Jordan, Turkey, KSA, and the Philippines. The findings confirmed that all 12 dimensions can be considered as areas requiring improvement, and these results demonstrated that there was a severe shortage in patient safety culture among the included hospitals.